Assessment of expressions of Bcl-XL, b-FGF, Bmp-2, Caspase-3, PDGFR-?, Smad1 and TGF-?1 genes in a rat model of lung ischemia/reperfusion - Simsek, Hasan; Demiryurek, Seniz; Demir, Tuncer; Atabay, Husne Didem; Ceribasi, Ali Osman; Bayraktar, Recep; Cengiz, Beyhan (Mashhad Univ Med Sciences, 2016)
Objective(s): Ischemia is described as organs and tissues are destitute of oxygen due to decreased arterial or venous blood flow. Many mechanisms play role in cell death happened as a consequence of a new blood flow is needed for both cell regeneration and to clean toxic metabolites during ischemia and later. Lung damage induced by ischemia/reperfusion (I/R) is a frequent problem in lung transplantation. Apoptosis (programmed cell death) is known as cell suicide, and plays a key role in embryonic developmental and in maintain adult tissue's life. Materials and Methods: It is investigated expressions of Smad1, Bmp-2, Bcl-XL, b-FGF, Caspase-3, TGF-beta 1, PDGFR-alpha genes for molecular changes in lung tissues, after I/R is formed, in this study. For this, we included 40 Wistar albino rats to this study and divided 4 groups (n=10). The Groups were determined as Control (C), Group 1=1 hr ischemia (I), Group 2=1 hr ischemia+ 2 hr reperfusion (I+2R), Group 3=1 hr ischemia+4 hr reperfusion (I+4R). Besides, molecular analysis and histopathologic examinations of tissues were performed, and the results were evaluated by normalization and statistics analysis. Results: We have found a significant increase in expression of Bcl-XL (P=0.046) and Caspase-3 (P=0.026) genes of group 1, and it was not monitored any significant difference in Group 2 and Group 3. In all groups, the changes in b-FGF (P=0.087), Bmp-2 (P=0.457), TGF-beta 1 (P=0.201) and PDGFR-alpha (P=0.116) were not significant compared to control group. We did not see any mRNA expression of Smad1 gene in all groups include control. Conclusion: These findings suggest that I/R injury may trigger apoptotic mechanism in lung.
Keywords: Apoptosis; Growth factors; Ischemia/reperfusion; Lung